Longitudinal relationships of metabolic syndrome and obesity with kidney function: Healthy Twin Study - Song, Yun-Mi; Sung, Joohon; Lee, Kayoung (Clinical and experimental nephrology, 2015)
Background To examine cross-sectional and longitudinal relationships, including genetic and environmental correlations, of metabolic syndrome (MetS) and obesity with kidney function. Methods Subjects were 3,437 Korean adults of the Healthy Twin Study for cross-sectional relationships and 1,881 participants for longitudinal relationships (follow-up interval 3.7 ± 1.4 years). Obesity (body mass index ≥ 25 vs. <25 kg/m 2 ), MetS, and chronic kidney disease [CKD; estimated glomerular filtration rate (eGFR) (<60 mL/min/1.73 m 2 using the modification of diet in renal disease study equation)] were categorized at baseline and follow-up. Results The prevalence and incidence of chronic kidney disease were 2.5 and 3.3 %, respectively. Compared to individuals without obesity and MetS, prevalent CKD was associated with MetS regardless of weight status [adjusted odds ratio (AOR) 4.19 for those with MetS but without obesity; AOR 4.63 for those with MetS and obesity]. Incident CKD was associated with obesity regardless of baseline metabolic status (AOR 2.03 for those with obesity but without MetS; AOR 2.85 for those with obesity and MetS). MetS at follow-up was associated with incident CKD regardless of baseline MetS (AOR 2.42–2.52). Sex-adjusted bivariate analyses show inverse environmental correlations of the number of MetS components and BMI at baseline, with eGFR at baseline and follow-up ( ρ E, −0.26 to −0.42, P < 0.001). Conclusions MetS predicts prevalent CKD regardless of obesity, and obesity predicts incident CKD regardless of baseline MetS. Incident CKD is also associated with MetS at follow-up regardless of baseline MetS. These associations appear to be explained by shared environmental factors.